Demand elasticities of canned tuna at point of sale of a large retail chain in southern Philippines implications for sustainability policy - Castro, Miko Mariz C.; Sarmiento, Jon Marx P.; Digal, Larry N. (Vol.150, No.4 (August 2021), pages 657-668.)
"New variants of canned skipjack tuna have been developed by large manufacturers of canned tuna in the Philippines. This study analyzes the expenditure and price elasticities of canned tuna and determines the implications for sustainable fishery. An AIDS (almost ideal demand system) model incorporating an income group variable was used to estimate these elasticities. This study utilized a pooled time series data of 459 weekly point-of-sale observations from 2010-2012 of three store branches of a large supermarket chain in southern Philippines"-title page.